Strategies to manage stress and fatigue in athletes - Wu, M.; Rossi, S.; Jiang, C.; Li, L. (Journal of Sport and Human Performance, 2018)
High level athletes frequently travel for competition, participate in heavy training loads, have dense competitive schedules, and have to manage pressure to perform. All of these are sources of stress and if not strategically managed could lead to fatigue, decreased performance, and increased risk for injury. The purpose of this review is to provide the reader scientifically based strategies to manage stress and promote performance. Specific attention will focus on the influence of travel, sleep, and training load.